2008
DOI: 10.1111/j.1399-0039.2008.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor gene polymorphisms and serum levels in Behçet’s disease

Abstract: Vascular endothelial growth factor (VEGF) is important for angiogenesis and inflammation, both of which are codependent and contribute to the pathophysiology of Behçet's disease (BD). In this report, we sought to investigate whether the selected VEGF polymorphisms [-634 C/G, +936 C/T and an 18 bp insertion/deletion (I/D) at -2549 of the VEGF promoter region] are associated with susceptibility and severity of BD in the Tunisian population. One hundred and thirty-five Tunisian BD patients and 157 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…For the -2549 I/D polymorphism, association of the I allele has been previously reported with BD in Italian patients (Salvarani et al, 2004) and with its severity in Tunisian patients (Kamoun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For the -2549 I/D polymorphism, association of the I allele has been previously reported with BD in Italian patients (Salvarani et al, 2004) and with its severity in Tunisian patients (Kamoun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene studies exploring associations between VEGF polymorphisms and circulating VEGF levels have yielded controversial results. Eight studies have found significant associations with candidate polymorphisms (rs699947, rs1570360, rs833061, rs2010963, rs3025039, and 2549 18 bp I/D) in the promoter, 5′- and 3′-UTRs of the VEGF gene (Renner et al , 2000; Awata et al , 2002; Krippl et al , 2003; Ferrante et al , 2006; Zhai et al , 2007; Kamoun et al , 2008; Petrovic et al , 2008). However, several other studies did not identify any association with these and other VEGF SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies have found significant associations with candidate polymorphisms (rs699947, rs1570360, rs833061, rs2010963, rs3025039, and 2549 18bp I/D) in the promoter, 5′, and 3′ untranslated regions of the VEGF gene [20–26]. However, several other studies did not identify any association with these and other VEGF SNPs.…”
Section: Discussionmentioning
confidence: 99%